The attributes of heritage, cultural, and creative tourism in the context of sustainability before and after the COVID-19 pandemic: A comprehensive review - Kittichai Kasemsarn (My University, 2024)
The activities and characteristics of heritage, cultural, and creative tourism are notably distinct despite the fact that they are frequently confused and misunderstood. Moreover, these types of tourism have been significantly affected by the COVID-19 pandemic. This review article aims to explore the characteristics of three types of tourism, both pre- and post-pandemic, and seeks to propose sustainable solutions with new opportunities for the tourism industry. The article adopts a PRISMA flow diagram and VOSviewer to perform a systematic literature review, ultimately selecting 179 articles from the Scopus, ScienceDirect, and Google Scholar databases and grouping them into five clusters: 1) heritage, cultural, and creative tourism; 2) co-creation; 3) creative city; 4) sustainability; and 5) technology and innovation. Consequently, this review article proposes a final framework presenting five related clusters suggesting sustainable solutions for creative tourism. It may aid the tourism industries in their transition to creative tourism, which is more sustainable and broadly focused while ensuring safety and enhancing income for local communities in the post-pandemic period.
Keywords: Sustainable Tourism; Pandemic; Heritage Tourism; Diverse Aspects of Tourism Research